The Relationship between Rostral Retraction of the Pannus and Outcomes at Cesarean Section - Turan, Ozhan M.; Rosenbloom, Joshua; Galey, Jessica L.; Kahntroff, Stephanie L.; Bharadwaj, Shobana; Turner, Shafonya M.; Malinow, Andrew M. (American Journal of Perinatology, 2016)
Objective Maternal obesity presents several challenges at cesarean section. In an effort to routinely employ a transverse suprapubic skin incision, we often retract the pannus in a rostral direction using adhesive tape placed after induction of anesthesia and before surgical preparation of the skin. We sought to understand the association between taping and neonatal cord blood gases, Apgar scores, and time from skin incision to delivery of the neonate.Study Design This is a retrospective study, performed using prospectively collected anesthesiology records with data supplemented from the patients' medical records. Singleton pregnancies with morbid obesity (body mass index [BMI] > 40 kg/m2) between 37 and 42 weeks of gestation who delivered via nonurgent, scheduled cesarean delivery under regional (spinal, combined spinal–epidural, or epidural) anesthesia between March 2007 and March 2013 were identified. Maternal demographics including BMI, comorbidities, type of anesthesia, time intervals during the surgery, cord gas results, and Apgar scores were collected. The relationship between taping and blood acid–base status, Apgar scores, and interval from skin incision to delivery was investigated using appropriate statistical tests.Results There were 2,525 (27.5%) cesarean deliveries out of 9,189 total deliveries. Applying the described inclusion/exclusion criteria, 141 patients were identified (33 taped and 108 nontaped). There was no significant difference in BMI between the taped (51.9 kg/m2) and nontaped groups (47.4 kg/m2), p > 0.05. There was no difference in type of anesthesia (p > 0.05). The only significant difference between the taped and not-taped groups was the presence of chronic hypertension in the taped group (p = 0.03). There were no significant differences in cord blood gas values, Apgar scores, or skin incision to delivery interval (p > 0.05 for all outcomes).Conclusions Taping of the pannus at cesarean section is a safe intervention that is not associated with adverse neonatal outcomes. Furthermore, over a set of parturients with BMI > 40 kg/m2, it does not hasten skin incision to delivery time.
Keywords: morbid obesity; retraction of pannus; cesarean delivery; neonatal outcome